Analisis Proses Penerimaan Barang di Gudang Produk Menggunakan Konsep Deming’s View Process System, Prinsip 5W + 1H dan Five Whys Analysis - M Hudori (JURNAL CITRA WIDYA EDUKASI, 2020)
The problem that often occur in the inbound process in the warehouse are process of unloading and late document making process and error in the process of inputting data in a computerized system. This ptoblem cannot be solved carefully is the root cause is not analyzed. The purpose of this research is to find out the deviations that occur in the inbound process, the root cause of the problem and solution. This research was conducted on February 22nd, 2018 – May 22nd, 2018 at a logistic company in Bekasi. Data analysis was processed by Deming’s View Process System concept, the 5W + 1H principle and the Five Whys Analysis. The result show that the root causes of problem are: 1) the supervisor and the assistant manager less supervision on the workers in the inbound section; 2) the supplier does not check the document when it will deliver the cargo; and 3) the workers have never been rewarded for their work. The solution is: 1) the supervisor and the assistant manager must supervise the workers in inbound section continuously; 2) the supplier must check the cargo and documents before being delivered the warehouse; and 3) the company must give a reward to the worker’s performance.